Analisis Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan - Ratna Riantiarna; Reno Septianingsih; Sabrini Lidiyawati; Saputra Saputra; Anggun Riaignasis Munthe; Bayu Putra Winata; Bahtiyar Heru Susanto (STIKes Ibnu Sina Ajibarang, 2024)
without any reference or formula. The quality of education is one of the problems that is and continues to be faced by the Indonesian people at every level and educational unit. School principals have a role in improving the quality and quality of education. In order to create quality education, what needs to be done is the role of leaders in educational institutions. one of them is the school principal who is able to drive all changes towards a better quality of education. However, of course, in this effort there are problems faced by school principals. The aim of this research is to describe the leadership of school principals to improve the quality of education and the problems they may face. This research method uses a literature review approach based on studies from several journals, proposals and books. The research results are based on a literature review of reward and punishment which has an effect on improving the quality of education in the leadership of school principals.